Analysis of Possibilities of Early Diagnostic Criteria for Parkinson’s Disease Based on Analysis of the Input–Output Curve - Janković, Marko V; Kačar, Aleksandra (Proceedings, Electrical engineering institute "Nikola Tesla", 2013)
In this paper, we analyse the possibilities of the diagnosis of Parkinson’s disease at an early stage, based on characteristics of the input–output curve. The input–output (IO) curve was analysed in two ways: we analysed the gain of the curve for low-level transcranial stimulation and we analysed the overall “quality” of the IO curve. The “quality” of the curve calculation is based on basic concepts from quantum mechanics and calculation of Tsallis entropy.